(untitled) (Journal of Dhaka Medical College, 2024)
Background: Polycystic ovary syndrome (PCOS) is an emerging endocrine condition that affects women of reproductive age all over the world. Physical activity (PA) is an evidence-based approach in the management of PCOS patients. Methods: This hospital-based case-control study was conducted to find out the association between physical activity and obesity with PCOS among the conveniently selected 172 women. Results: The mean age of PCOS women was 25.0±5.8 years and non-PCOS women was 28.1±7.5 years. The majority of cases (84.9%) were in the 15-30 age groups, in comparison to controls (64.0%). There was a significant association between age and PCOS (p<0.05). The chance of developing of PCOS was 3.1 times higher in the younger age group. More than half of cases (65.5%) had no child, in comparison to controls (72.4%) had a child. There was a significant association between the number of children and PCOS (p<0.05). The chance of infertility among PCOS women was 2.01 times higher than among non-PCOS women. About one-third of the cases (39.5%) had a normal BMI and 37.2% were overweight. In contrary among controls, about half (59.3%) had a normal BMI, and one-fourth (25.6%) were overweight. The association between BMI and PCOS was statistically significant (p<0.05). The chance of developing of PCOS was 3.38 times higher in overweight women. The mean total sitting time/week in PCOS women (3179.76±1511.46) was higher than in non-PCOS women (2647.67±1687.74). There was a statistically significant association between total sitting time and PCOS in women (p<0.05). Conclusion: There was a significant association between PCOS and BMI, indicating that overweight women are at greater risk to develop PCOS. However, no association was found between physical activity and PCOS, whereas PCOS patients sitting longer per week. J Dhaka Med Coll. 2023; 32(1) : 16-24